274 COMPARISON OF THE OUTCOMES OF WORLD HEALTH ORGANIZATION CLASS III LUPUS NEPHRITIS TREATED WITH CYCLOPHOSPHAMIDE OR MYCOPHENOLATE MOFETIL AS INDUCTION THERAPY IN PEDIATRIC PATIENTS. Issue 1 (1st January 2007) - Lau, K.; Haddad, M.; Jones, D.; Ault, B.; Butani, L.
Abstract : Purpose: To determine the efficacy of mycophenolate mofetil (MMF) versus cyclophosphamide (CTX) as induction therapy for the first 6 months in pediatric patients with class III lupus nephritis (LN). Introduction: Renal involvement is one of the major determinants of the outcome in patients with systemic lupus erythematosus. Information on the optimal treatment of pediatric patients with class III LN is still very limited. Although CTX has been used with success in pediatric patients with class III lupus, MMF may be a better alternative with less toxicity. Methods: We retrospectively studied patients with histologic diagnosis of class III LN from two pediatric centers from January 1990 to December 2005 who were either treated with monthly intravenous (IV) CTX or oral MMF for the first 6 months. All patients were below age 18 at the time of biopsy. Clinical features assessed included age, gender, race, serum creatinine (Cr), estimated glomerular filtration rate (GFR), blood pressure, urine protein to creatinine ratio (UPC), complement 3 and 4 levels, serum albumin, hemoglobin, renal histology, and prednisone doses. Complete remission (CR) is defined as normal clinical and laboratory findings, including normal urinalysis; partial remission (PR) refers to improved but not normal parameters and a UPC of < 1. Not in remission (NR) refers to a UPC > 1. Results: Thirteen patients were studied. The CTX group had seven patients and 71% had hypertension. The MMF group had six patients and 33% were hypertensive. Although the CTX gruop had higher mean serum creatinine and UPC (1.4 mg/dL and 6, respectively) than the MMF group (0.7 mg/dL and 1.1), the differences were not statistically significant. At 6 months, there were no differences in any laboratory parameter between the two groups. In the CTX group, no patients had achieved CR, 57% had PR, and 43% had NR. In the MMF group, 66% had achieved CR, 17% had PR, and 17% had NR; the differences were not significant. One patient in the CTX but none in the MMF group had GFR < 60 mL/min/1.73m 2 . However, at the last follow-up, in the CTX group, 57%, 14%, and 29% had CR, PR, and NR, respectively; in the MMF group, 17% and 50% had CR and PR, respectively; 17% of patients were switched to oral CTX and 17% had renal failure that required dialysis. No complication was observed in either gp. Conclusions: In a small group of children with class III LN, 6-month outcomes are equivalent with either IV CTX or MMF, and there was no difference in the incidence of complication.